Food and agribusiness yearbook & directory. (University of Asia and the Pacific, 2000)
Purpose:"For the past 12 years, the food and agri-business yearbook and directory have profiled agricultural commodities, covered statistics on national economy, trade, minimum access volumes, tariffs, agricultural production and prices. It has also developed an extensive directory of relevant firms. This publication can help many stakeholders in making more informed business decisions."